Visionary Leadership Grounded in Islamic Values and Digital Innovation in Islamic Educational Institutions: Kepemimpinan Visioner Berbasis Nilai-nilai Islam dan Inovasi Digital di Lembaga Pendidikan Islam - Sjah, Novy Real Vyanti; Rahmawati, Imelda Dian (Indonesian Journal of Innovation Studies, 2026)
General Background: Rapid digital transformation requires visionary leadership in Islamic educational institutions that combines technological development with moral and spiritual values. Specific Background: Such leadership is expected to build strategic, adaptive, and ethical institutional directions based on the Qur’an and Sunnah. Knowledge Gap: Previous discussions of visionary leadership have not sufficiently integrated Islamic values with digital innovation in Islamic educational contexts. Aims: This study analyzes the characteristics, implementation, challenges, and role of visionary leadership grounded in Islamic values and digital innovation. Results: Using qualitative library research, the study identifies strategic vision, integrity, collaboration, data-based decision-making, digital competence, and continuous adaptation as key characteristics. Novelty: The study integrates tauhid, amanah, justice, and consultation with digital innovation within visionary educational leadership. Implications: Continuous training, ethical digital practices, collaborative communities, strategic partnerships, and data-based evaluation are needed to support sustainable institutional development. Key Findings Highlights Strategic direction requires integrity, collaboration, communication, and future-oriented thinking. Tauhid, amanah, justice, and consultation provide the moral foundation for institutional decisions. Resistance, limited technological competence, and financial constraints remain major implementation challenges. Keywords : Visionary Leadership, Islamic Education, Islamic Values, Digital Innovation, Educational Institutions